L'effet de l'épigénétique sur la production et reproduction de la vache laitière dans la région de GURRARA W.GHARDAIA - BASLIMANE, DJAMEL EDDINE (My University, 2018)
This study analyzes the effect of epigenetic essentially temperature on milk production in terms of quantity and reproduction of fertility point of view in a farm located in the Guerrara region of Ghardaia wilaya. The research involved the monitoring of milk production of 53 dairy cows of the Holstein breed (black foot and red foot), which has the same age and the same stage of lactation and a living weight that is approaching. The results obtained in evidence that the factor studies (precisely epigenetic: temperature) has a significant influence on the average daily milk production and significantly on the quantity of flakes consumed to international standards.
Keywords: épigénétique; température; vache; production de lait; fertilité; epigenetics; temperature; cow; milk production; fertility